2011
DOI: 10.1016/j.ajpath.2011.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Lung-Targeted Overexpression of the NF-κB Member RelB Inhibits Cigarette Smoke–Induced Inflammation

Abstract: Acute lung inflammation can be caused by a variety of respirable agents, including cigarette smoke. Longterm cigarette smoke exposure can cause chronic obstructive pulmonary disease (COPD), a serious illness that affects >10 million Americans. Cigarette smoke is a known inducer of inflammation and is responsible for approximately 90% of all COPD cases. RelB, a member of the NF-B family, attenuates cigarette smoke-induced inflammatory mediator production in mouse lung fibroblasts in vitro. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 66 publications
1
51
1
Order By: Relevance
“…Aryl hydrocarbon receptor-deficient fibroblasts exposed to cigarette smoke showed increased expression of cyclooxygenase-2 and prostaglandins, in association with a loss of RelB (41). Indeed, an anti-inflammatory role for RelB in cigarette smoke-induced inflammation was recently demonstrated, as evidenced by decreased neutrophilic infiltration and the diminished content of proinflammatory mediators after the adenovirus-mediated transduction of RelB (42). In response to LPS, RelB 2/2 fibroblasts showed prolonged increases in proinflammatory cytokines compared with wild-type controls, suggesting a role for RelB in the resolution of inflammatory responses (43).…”
Section: Discussionmentioning
confidence: 99%
“…Aryl hydrocarbon receptor-deficient fibroblasts exposed to cigarette smoke showed increased expression of cyclooxygenase-2 and prostaglandins, in association with a loss of RelB (41). Indeed, an anti-inflammatory role for RelB in cigarette smoke-induced inflammation was recently demonstrated, as evidenced by decreased neutrophilic infiltration and the diminished content of proinflammatory mediators after the adenovirus-mediated transduction of RelB (42). In response to LPS, RelB 2/2 fibroblasts showed prolonged increases in proinflammatory cytokines compared with wild-type controls, suggesting a role for RelB in the resolution of inflammatory responses (43).…”
Section: Discussionmentioning
confidence: 99%
“…Adult female C57BL/6J mice were purchased from The Jackson Laboratory (Bar Harbor, ME) and housed in the Inhalation Core Facility at the University of Rochester. Mainstream CS exposures were as previously described (35,61,62). Mice were placed in individual compartments of a wire cage that was placed inside a closed plastic box connected to the smoke source.…”
Section: Methodsmentioning
confidence: 99%
“…CS contains high levels of free radicals and other reactive oxygen species (ROS) that contribute to proinflammatory activation of lung cells via NF-B and other redox-sensitive transcription factors (10,35,52,53). Additional ROS, including superoxide, H 2 O 2 , and hypochlorus acid, are released by inflammatory macrophages and neutrophils via the action of enzymes, including xanthine/xanthine oxidase, myeloperoxidase (MPO), and NADPH oxidase (30,69).…”
mentioning
confidence: 99%
“…Recently, studies have reported that RelB diminished cigarette smoke-induced COX-2 protein expression in lung fibroblasts, attenuating inflammation (46). The overexpression of RelB suppressed the inflammatory response and protected against lung injury (47). Therefore, we screened p65, p50, and RelB to clarify the role of NF-kB in the inflammation-resolving activity of COX-2.…”
Section: Figurementioning
confidence: 99%